Evolusi Institusi Pendidikan Islam Klasik Evolution of Classical Islamic Education Institutions - Muhammad Yunus Ibrahim (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2020)
This article aims to export the History of Islamic Education which has lasted approximately 14 centuriesago, that is, since the prophet Muhammad was sent to be an apostle. Initially education took place simply,with the mosque as the center of the learning process, the Koran and Hadith as the main curriculum of theProphet himself acted as a teacher in the education process, but after the Prophet's death Islam continuedto develop to the end of the Arabian peninsula. Islamic educational institutions are very important inachieving the success of the education process, because the institution functions as a mediator inregulating the course of the educational process. Nowadays it seems that education cannot be called ifthere is no institution. Because education plays a central role in Islam. Science becomes the backbone ofIslamic teachings. More than 800 verses of the Qur’an mention, allude or discuss the importance of science.Just a comparison, only 90 Qur'anic verses discuss fiqh or Islamic jurisprudence. Islamic education, is veryclosely related to educational institutions because an Islamic education has an institution that helps.Islamic educational institutions are a place or place where the process of Islamic education takes placesimultaneously with the process of civilization, and it starts from the family environment.